Non-adiabatic generation of NOON states in a Tonks–Girardeau gas ☆Dedicated to the memory of Marvin D Girardeau. (22nd March 2016) - Schloss, James; Benseny, Albert; Gillet, Jérémie; Swain, Jacob; Busch, Thomas
Abstract: Adiabatic techniques can be used to control quantum states with high fidelity while exercising limited control over the parameters of a system. However, because these techniques are slow compared to other timescales in the system, they are usually not suitable for creating highly unstable states or performing time-critical processes. Both of these situations arise in quantum information processing, where entangled states may be isolated from the environment only for a short time and where quantum computers require high-fidelity operations to be performed quickly. Recently it has been shown that techniques like optimal control and shortcuts to adiabaticity can be used to prepare quantum states non-adiabatically with high fidelity. Here we present two examples of how these techniques can be used to create maximally entangled many-body NOON states in one-dimensional Tonks–Girardeau gases.